Влияние режимов ионного легирования и фотонного отжига на параметры имплантированных слоев n-GaAs:Si - Bonchyk, A. Yu.; Izhnin, I. I.; Kyjak, S. G.; Savytsky, G. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The paper presents the results of studies on the influence of ion implantation regimes and pulsed incoherent photon annealing on the parameters of Si-implanted n-GaAs layers grown on semi-insulating GaAs substrates. The obtained layers are characterized by the following parameters: thickness of 0.1–0.3 μm, electron concentration of 1017–1018 cm−3, and mobility of 2000–3000 cm2/(V·s).